2003
DOI: 10.1046/j.1365-2648.2003.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in people with intellectual disabilities: the impact of nurse‐led health screenings and health promotion activities

Abstract: Health screening per se has limited impact on reducing obesity levels in this client group. Rather, health personnel such as general practitioners, nurses and health promotion staff need to work in partnership with service staff, carers and people with intellectual disabilities to create more active lifestyles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 16 publications
8
111
0
6
Order By: Relevance
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Based on actual measurements of body weight and height of 183 British men and women with ID living with other family members, Bell and Bhate [1992] found that 19.0% of men and 34.6% of women were obese (i.e., BMI Ն 30). In a sample of 321 adults with ID who resided in Northern Ireland, Marshall et al [2003] reported that 32% were obese (BMI Ն 30), and 4.2% were classified in the extremely obese category (BMI Ն 40). In a sample of adults with ID (n ϭ 202) residing in Sydney, Australia, 16.3% of men and 26.5% of women were obese (i.e., BMI Ͼ 30).…”
Section: Obesity Prevalence In Adults With Id Outside the United Statesmentioning
confidence: 99%
“…Obesity is a significant health problem within the intellectual disability population (Blair and Nichaman, 2002), as a higher proportion are overweight or obese compared with the general population (Marshall et al, 2003;Draheim, 2006). The Centres for Disease Control and Prevention (CDC) reports this rate is higher by 59% (CDC, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Health promotion aims to enable people to gain control over their lives (World Health Organization (WHO), 1986) and refers to health in a broad sense including physical, mental and social health (Ewles and Simnett, 2010) focusing on primary, secondary and tertiary prevention (Hart, 2007). Within intellectual disability, the emphasis in health care has predominantly been directed at the primary disability rather than on prevention or reducing secondary health conditions (Marshall et al, 2003). This emphasis on prevention or management of disability may indicate a possible reason why health promotion issues have not been addressed for people with an intellectual disability (Rimmer, 2002), and terms such as 'wellness' and 'health promotion' are not often associated with this population (Rimmer, 1999;Marshall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%